High ligation of the saphenofemoral junction is necessary! - Mumme, A.; Hummel, T.; Burger, P.; Frings, N.; Hartmann, M.; Broermann, M.; Schwahn-Schreiber, C.; Stenger, D.; Stücker, M. (Phlebologie, 2009)
Neovascularisation can compromise the success of high ligation and resection of the greater saphenous vein. Studies using duplexultrasound to classify recurrent groin veins have described rates of neovascularisation as high as 60% and raised the question whether high ligation is actually able to prevent groin recurrences. In the present study, recurrent groin veins were excised and examined histologically in order to prove whether neovascularisation is the main cause for sapheno-femoral recurrences. Patients, methods: 419 patients accounting for 458 legs with clinically symptomatic groin recurrences were included in a country-wide multicenter study. The recurrent groin veins were excised in a standardized fashion and subsequently divided into the different types of recurrence based on histopathological criteria. Results: 427 specimen (93%) were available for histopathological examination. In 69 cases (16.2%) a neovascularisation was found to be the cause of recurrence. 311 specimen (72.8%) contained a long residual stump of the greater saphenous vein, out of which 32 (7.5%) showed additional neovascularisation at the site of the ligation. In 29 cases (6.8%) a venous side branch was found to be the recurrent groin vein. 11 specimen (2.6%) did not contain any evidence of venous material and in another 7 cases (1.6%) it was not possible to clearly identify the cause of recurrence during the histo pathological workup. Conclusion: The high rates of neovascularisation described in several duplex ultrasound studies could not be confirmed in our investigation. Recurrences seem to be mainly caused by a technically incorrect initial operation which leaves a long residual stump of the saphenous vein in place. Following a technically correct high ligation, clinically relevant recurrences appear to be rare. This finding underlines the necessity of a high ligation of the saphenous vein according to current guidelines.
Keywords: High ligation; neovascularisation; varicose vein; groin recurrence; technical error